Indo-Iranian Terms Denoting Time - Nandhikkara, Jose; Luke, K (Journal of Dharma, 1976)
Sanskrit and Iranian are in possession of a number of terms that denote either time2 as such or some specific and concrete division of it. It is the purpose of the present Paper to study in depth a couple of noun forms defining time in its abstract, durational, and momentary or punctual aspects, namely, samaya-kala-kalpa-and mubu- and its derivatives. Lest the study should become too unwieldy, we shall consider from Iranian only xrvan-, the usual word for time in Avestan. The method of approach will be philological, and an endeavour will be made to trace briefly the semantic evolution of the individual terms. Before passing on to the topic of our paper we wish to point out that IE, verbs, no matter whether they are finetive or stative, had originally only aspects and not tenses in the strict sense, and it would therefore be a mistake to think that the earliest sources at our disposal for the study of the Indo-Iranian vocabulary of time embody abstract and philosophical notions.